Oportunities and Dimensions of a Romanian Environment Code - Mircea Dutu (Theoretical and Applied Economics, 2006)

(untitled)
Codifying the environmental law is required both by the natural evolution trend of this relatively new branch of law and by the need to rationalize the legislation and halt the regulatory inflation, the legislative instability and their corollary – failure to apply the existing legal norms. After undertaking the acquis communautaire and after the accession of Romania to the EU, the transition process post-1989 of environmental legislation and policy would generally be complete, increasing the opportunity for stable regulations in this field and would favour their codification, which becomes an objective of European integration and an important political option. In relation to the size of the reform to be adopted with this regard, the technical method to be applied can be determined – by simple „compillation”, by regrouping the texts in force, by codifying the existing law or by reforming codification, followed by the establishment of the general plan and setting the area of coverage of the Code. Codification is a method of development of environmental law, already chosen by former comunist countries such as the Czech Republic and Poland, while in Romania the concept has been launched by specialists and accepted by the Minister of environment.